Auctions as Collusion Devices - Maarten C.W. Janssen (Tinbergen Institute, 2003)
This paper develops an economic argument relating auctions to high marketprices. At the core of the argument is the claim that market competition andbidding in an auction should be analyzed as part of one game, where the pricingstrategies in the market subgame depend on the bidding strategies during theauction.I show that the only equilibrium in the overall game that is consistentwith the logic of forward induction is the one where firms bid an amount(almost) equal to the profits of the cooperative market outcome and follow acooperative pricing strategy in the market game resulting in high prices.
Keywords: L50; 330; auctions; market collusions.; Auktionstheorie; Lizenz; Wettbewerbsbeschränkung; Preismanagement; Theorie